Verkehrskosten der Randwanderung privater Haushalte - Scheiner, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
Location-specific costs are of major significance for a private household’s location decisions. The paper estimates the additional transport costs a household has to face as a consequence of residential suburbanisation. The major components of these costs are changes in household motorisation and travel distances covered by specific modes. The results indicate significant increases in transport costs as an effect of suburbanisation. The increase is particularly strong for employees and households purchasing (an) additional automobile(s). A household composed of one employee and one non-employed individual who purchases one additional car has to expect additional transport costs ranging between 350 and 400 € per month, depending on the chosen location.